Characteristics of adults with autism spectrum disorder who use residential services and supports through adult developmental disability services in the United States. (February 2017) - Hewitt, Amy S.; Stancliffe, Roger J.; Hall-Lande, Jennifer; Nord, Derek; Pettingell, Sandra L; Hamre, Kristin; Hallas-Muchow, Libby
Highlights: In a random sample of 11, 947 users of adult IDD services in 25 states, 1459 had an autism diagnosis (12%). There was a significant association between living arrangement and ASD status. Accounting for demographic and state, those with ASD had 26% higher odds of living with family but 44% lower odds of living in their own home. Participants with ASD who received services were significantly younger and had significantly higher levels of challenging behavior than those without ASD. Abstract: Background: Many children and adults with Autism Spectrum Disorder (ASD) need services and support across their lifespans. Currently many residential and community living supports are delivered through state intellectual and developmental disabilities (IDD) service systems. Method: A random sample of 11, 947 individual users of adult IDD services from 25 states that included 1, 459 individuals with an autism diagnosis was analyzed for this study looking at demographic characteristics and living arrangements. Comparisons were made between adults with and without ASD who receive services through the IDD service system. Results: Overall, individuals with an ASD diagnosis were younger on average, had a higher percentage of males, and had higher percentages of the No Intellectual Disabilities (ID) and Severe ID categories compared to individuals without an ASD diagnosis. There was a significant association between the type of living arrangement and ASD status with a higher percentage of participants with ASD living in a family member's home, but a lower percentage of people with ASD living in agency apartments, in their own home or an "other" living arrangement. However, with age, gender, and level of ID and challenging behavior taken into account, people with ASD had 29% higher odds of living in a family member's home but 42% lower odds of living in their own home when compared to people with other developmental disabilities who received residential services through state IDD service systems. Conclusions: There are key differences in access and utilization of residential services between people with ASD and people without ASD. While state developmental disabilities systems are serving individuals with ASD there are potential influences of state policies regarding ASD eligibility for various residential services. Implications for future research are discussed.